2020
DOI: 10.1007/s00520-019-05269-z
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally inserted central catheters in allogeneic hematopoietic stem cell transplant recipients

Abstract: Background Central venous catheters (CVC) are essential for the management of patients with hematologic malignancies, facilitating chemotherapy infusion, antibiotics, parenteral nutrition, blood products, and blood samples collection. In this population, peripherally inserted central catheters (PICC) seem to be associated with lower complications, compared with conventional percutaneously inserted devices (CICC). Data on the PICC in allogeneic hematopoietic stem cell recipients (allo-HSCT) are limited. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
2
12
1
Order By: Relevance
“…Some studies have reported the safety and usefulness of PICCs for hematologic diseases, including stem cell transplantation (25,(27)(28)(29); our study also showed safe and effective profiles. Although a PICC can be used in chemotherapy, blood transfusion, and parenteral nutrition to avoid problems associated with the use of a conventional CVC, PICCs were found to be inconvenient in cases in the present study requiring bolus injection, such as during intensive care, resuscitation, or stem cell infusion.…”
Section: Discussionsupporting
confidence: 66%
“…Some studies have reported the safety and usefulness of PICCs for hematologic diseases, including stem cell transplantation (25,(27)(28)(29); our study also showed safe and effective profiles. Although a PICC can be used in chemotherapy, blood transfusion, and parenteral nutrition to avoid problems associated with the use of a conventional CVC, PICCs were found to be inconvenient in cases in the present study requiring bolus injection, such as during intensive care, resuscitation, or stem cell infusion.…”
Section: Discussionsupporting
confidence: 66%
“…Most studies are single-institution studies and demonstrate that PICCs are safer than CVCs in terms of the risk of catheter-related complications and CRBSI. While the evidence is limited, some studies demonstrated that the use of polyurethane catheters in allogeneic hematopoietic stem cell transplant recipients 20 and acute leukemia in adults are risk factors of CRBSI 21 . Similarly, our findings also suggest that patients with progressive diseases may be at a higher risk for CRBSI.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral vein insertion of PICC [11,12] have reported the incidence of PICC-related CRBSI is between 8.11 and 12.35%. The results of this study have shown that the incidence of CRBSI in our department is 10.62%, which is consistent with the results of related studies.…”
Section: Discussionmentioning
confidence: 99%